Identifikasi Waste Guna Mengefisiensikan Proses Produksi Castable di PT. Benteng Api Technic Gresik - Novitasari, Etika Devi; Murnawan, Hery (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
PT Benteng Api Technic was founded in 1997 and produces refractory bricks, refractory cement and various refractory materials. Refractory cement or castable currently still uses a pre-order system before the production process is carried out. During observations for seven days with 38 observations, there were activities that were felt to be less efficient, then the value stream mapping method was carried out to streamline waste. The result is a defect when the production process is finished, there is a repetition of the production process because it does not pass the feasibility test, processing because a lot of leftover material falls in the bagging section and the material is no longer used. Waiting is the average part of weighing materials/products of 1.54 seconds (waiting for the material composition recipe and weighing platform trouble/error). Material mixing section with an average/product of 1.82 seconds (waiting for machine repairs due to leaking air duct). Total production lead time is 3396 seconds. Once the waste is identified, the next step is to eliminate the activity by testing data adequacy and testing data uniformity. The results of the analysis of the castable production process contained 2 analyses, the first analysis by reducing activity time with an average total time of 3285 seconds/44 cement and the second analysis by reducing and eliminating the cement weighing activity in the bagging section with a total time of 2873 seconds/44 cement